The service sector and carbon emission nexus: revisiting Environmental Kuznets Curve - Jain Yassin,; Sarma Aralas, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to examine the expansion effects of the service sector on the carbon emission in a dynamic non-linear model. Using data of 34 Asian countries ranging from 1990 to 2016, this study adopts non-linear model of the Environmental Kuznets Curve and the GMM estimator. The finding provides evidence of an N-shape association between the service sector and carbon emission which indicates that the growth of the service sector fails to reduce the carbon emission perpetually. The elasticity of urbanisation and trade openness are found to be positive which indicates that an increase in urbanisation and trade openness significantly intensifies carbon emission. Meanwhile, an increase in the ageing population tends to mitigate carbon emission in Asian countries. This current study facilitates the understanding of the impact of the services sector on carbon emission as well providing a solid ground in designing a policy that incorporates the environmental standard in line with increased economic growth.